Afrokology and the Right to Communicate in Africa - Viola, C., Milton; Winston, Mano (Javnost-The Public, 2022)
This article argues for a reconstruction of communication rights theories from an African episteme and experience. It reviews the impact of key national, continental and international legal instruments as they pertain to communication rights in Africa, with a specific focus on South Africa and Zimbabwe. Using an Afrokological heuristic tool, it critically evaluates how the key legal instruments underpinning the right to communicate are developed and encountered in lived experience in decolonising Southern African contexts. We argue that an Afrokological orientation built on epistemological interconnectedness and conviviality may lead to insights otherwise not accessible. It can help awaken a new relational accountability that promotes respectful representation, reciprocity, and rights in communication policy processes in line with the lived experiences of those it is meant to benefit.